2006
DOI: 10.1016/j.jcrs.2006.01.092
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of intraocular lens movement and dioptric change with a focus shift accommodating intraocular lens

Abstract: Small forward movement of the 1CU IOL was seen with accommodation and increased following pilocarpine, compared to the posterior movement of the MA30 IOL. The amount of the IOL shift was not sufficient to provide useful near vision, but the difference suggests that the engineering concept behind the 1CU IOL is valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…The duration of follow-up ranged from 4 weeks to 3 years, with most being at least 1 year. Attrition was significantly high (O30%) in 3 16,20,23 of the 7 studies that reported dropout rates. Only 3 trials reported using more than 1 blinding method (examiner-and patient-masked).…”
Section: Description Of Studiesmentioning
confidence: 97%
“…The duration of follow-up ranged from 4 weeks to 3 years, with most being at least 1 year. Attrition was significantly high (O30%) in 3 16,20,23 of the 7 studies that reported dropout rates. Only 3 trials reported using more than 1 blinding method (examiner-and patient-masked).…”
Section: Description Of Studiesmentioning
confidence: 97%
“…The mechanism of action varies between the various single optic accommodative IOLs, and is dependent on ciliary muscle contraction either producing an increase in vitreous fluidic pressure19 (pushing the lens forward) or releasing the zonule tension and allowing the elastic capsular bag to press upon the IOL haptics. 19 The accommodative amplitude of these IOLs is limited by the power of the IOL and can be reduced further with capsular opacification, as this reduces capsular bag elasticity.…”
Section: Accommodating Intraocular Lensesmentioning
confidence: 99%
“…76 Several biometric techniques have been employed including high frequency ultrasonic biomicroscopy, 77 partial coherence interferometry, 60,78,79 Scheimpflug imaging using the IOLMaster (Carl Zeiss, Jena, Germany) 28,80 and anterior segment optical coherence tomography (AS-OCT). 81 Furthermore, a new optical low coherence reflectometry device is now available (LenStar, HaagStreit or Allegro Biograph, Wavelight) 82,83 that can measure lens position to a resolution of 0.01 mm.…”
Section: Analysis Of Optic Movementmentioning
confidence: 99%
“…Distance-corrected near vision (DCNV) was significantly better in the 1CU group than the control group in three of these studies, 61,103,104 although two investigations failed to detect any difference in DCNV between the implant groups. 60,78 Over time, the accommodative ability of the 1CU may decrease and the enhanced near visual function provided by the implant has been found to be reduced at 12 105 and 24 months. 59 Those studies which have analysed axial optic movement in response to pilocarpine stimulation have found significantly more forward shift with the 1CU than the non-accommodative implants, although the maximum mean anterior movements reported for the AIOL are -0.82 Ϯ 0.3 mm in a randomised control trial 61 and -0.83 Ϯ 0.25 mm in a non-randomised study.…”
Section: Cumentioning
confidence: 99%